THE EFFECT OF GREEN WORK ENGAGEMENT, EMPLOYEE GROWTH MINDSET, AND EMPLOYEE'S INNOVATIVE WORK BEHAVIOR ON INNOVATIVE ORGANIZATIONAL CULTURE - Sri Huning Lestari; Widiya Dewi Anjaningrum (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
An innovative organizational culture presents an opportunity for commercial entities to maintain competitiveness, particularly within the MSME sector. Consequently, MSME entrepreneurs must devise ways to confront competition. This study seeks to elucidate the impact of the interplay among Green Work Engagement, Employee Growth Mindset, and Employee Innovation Work Behavior on the Innovation Organizational Culture within Patchwork and Quilting MSMEs in East Java. The study population comprised all Patchwork and Quilting MSMEs in East Java, the exact number of which is unspecified. Respondents were chosen using unintentional purposive sampling, with quantitative data gathered from 160 individuals in the Patchwork and Quilting MSME sector in East Java. This study, utilizing PLS-SEM, demonstrated that the three independent factors positively influence Innovation Organization Culture in all Patchwork and Quilting MSMEs in East Java. The findings indicate that green employee engagement substantially fosters the development of an innovative organizational culture. Furthermore, employees possessing a growth mindset can facilitate innovative collaboration through their work behavior, ultimately cultivating a more innovative work environment and promoting sustainable organizational growth. This study offers comprehensive insights and tangible advantages for MSME stakeholders in formulating new human resource development strategies that are competitive in the current era.